2021
DOI: 10.1002/ece3.8407
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific risk assessment enables trade‐off analysis of non‐native tree species in European forests

Abstract: For centuries, non-native tree species ("NNT") (Box 1) have been introduced to and cultivated in Europe, and now 4% of the European forest area is covered by more than 150 NNT (Brus et al., 2019).The major drivers for the use of NNT in forests are the economic benefits linked to their often better growth performance, timber properties, and pest resistance in comparison to native tree species (Pötzelsberger, Spiecker, et al., 2020). NNT are valued for their contribution to diversifying the portfolio of commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 196 publications
0
8
0
Order By: Relevance
“…(own field observation described in de Groot et al, 2022). Nevertheless, no non-native tree species can be grown without risks and professionals in forestry and conservation are fighting together against some undoubted invasive tree species, e.g., tree of heaven (A. altissima), suggesting the need for sitespecific risk assessment (Bindewald et al, 2021). The concept of UNESCO Biosphere Reserves offers spatially separated various management options for the three zones, but the spread of species across zones and country borders demands a coherent management framework targeting at potentially invasive or harmful species (as well as other cross-border ecological interactions that were not mentioned in this study such as water dynamics or wildlife preservation).…”
Section: Tree Species Selection In the Context Of Environmental Changementioning
confidence: 99%
“…(own field observation described in de Groot et al, 2022). Nevertheless, no non-native tree species can be grown without risks and professionals in forestry and conservation are fighting together against some undoubted invasive tree species, e.g., tree of heaven (A. altissima), suggesting the need for sitespecific risk assessment (Bindewald et al, 2021). The concept of UNESCO Biosphere Reserves offers spatially separated various management options for the three zones, but the spread of species across zones and country borders demands a coherent management framework targeting at potentially invasive or harmful species (as well as other cross-border ecological interactions that were not mentioned in this study such as water dynamics or wildlife preservation).…”
Section: Tree Species Selection In the Context Of Environmental Changementioning
confidence: 99%
“…The recent IPBES thematic assessment of non‐native species concluded that filling data gaps, including on impacts, can bring about important improvements in the cost‐effectiveness and success of prevention and management actions (IPBES, 2023). EICAT can provide valuable data on the impacts of non‐native taxa, which can feed into policymaking and management decisions (e.g., Bindewald et al., 2021; Coville et al., 2021; Kumschick, Bacher, et al., 2020; Kumschick, Wilson, et al., 2020). EICAT is used as a decision‐support tool for non‐native species management in its application in national lists, for example, in South Africa (Kumschick, Wilson, et al., 2020), Switzerland (FOEN, 2022), and Italy (Bertolino et al., 2020), in cities such as Cape Town, South Africa (Gaertner et al., 2017), and in the Spanish network of protected areas (Gallardo & Capdevila, 2018).…”
Section: Final Considerationsmentioning
confidence: 99%
“…Within the group of species with potential negative impact in the context of urban areas, we defined two groups, species with invasive potential and species with allergenic potential, both of relevance in the context of Skopje. The invasive potential of allochthonous species is an active discussion in forestry (Pötzelsberger et al 2020b, Bindewald et al 2021, Dimitrova et al 2022), but it is also important in urban areas. Over the centuries and with the increase of anthropogenic mobility, due to their exotic nature, many allochthonous species were primarily introduced in urban areas from where they could disperse and employ both active and passive invasive mechanisms (Trusty et al 2007, Deparis et al 2022.…”
Section: Potentially Risky Species -Negative Impactmentioning
confidence: 99%